Responsible AI Development: A Comprehensive Framework for Ethical Implementation in Contemporary Technological Systems - Ravi Kottur, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article presents a comprehensive framework for implementing responsible artificial intelligence (AI) development in contemporary technological landscapes. As AI systems become increasingly integrated into daily life across various sectors, the need for ethical guidelines and responsible development practices has become paramount. The article examines the fundamental principles of responsible AI, including fairness, transparency, accountability, privacy, and system robustness, while proposing practical implementation strategies for organizations. Through analysis of current practices and emerging challenges, this article outlines a structured approach to ethical AI development that balances innovation with societal values. The article introduces a multi-stakeholder model for implementing responsible AI practices, emphasizing the importance of cross-disciplinary collaboration, continuous education, and robust oversight mechanisms. By examining the intersection of technological advancement and ethical considerations, this article contributes to the growing body of knowledge on responsible AI development and provides actionable insights for developers, policymakers, and organizations. The findings suggest that successful implementation of responsible AI requires systematic integration of ethical principles throughout the development lifecycle, supported by strong governance frameworks and stakeholder engagement.
Keywords: Responsible Artificial Intelligence; Ethics Framework; Technological Governance; Algorithmic Accountability; Digital Innovation Ethics